2020
DOI: 10.1111/ipd.12729
|View full text |Cite
|
Sign up to set email alerts
|

Structuring adolescent’s oral health effects on labour market entry in a cohort study

Abstract: Aim To evaluate the influence of the oral conditions and oral health‐related quality of life (OHRQoL) on the entry of adolescents on labour. Design This cohort study was performed in southern Brazil, within a random sample of 12‐year‐old adolescents (n = 1134). Oral health (dental caries, malocclusion, and toothache), OHRQoL (Child Perceptions Questionnaire 11‐14), demographic factors, and family's socioeconomic status (household income and mother's education) were collected at baseline (2012). Education level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, use of pit and fissure sealants prevents dental caries in adolescents ( 24 , 54 , 71 73 ). On the other hand, dental caries and oral health status of adolescents may affect school performance ( 74 ), school absenteeism ( 21 ), and future employment outcome ( 75 ), and consequently health literacy and use of dental care. Finally, other habits, such as smoking ( 35 , 60 , 65 , 66 ) and use of snuff or smokeless tobacco ( 60 ), are also risk factors, as tobacco exposure ( 76 ) is associated with dental caries among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, use of pit and fissure sealants prevents dental caries in adolescents ( 24 , 54 , 71 73 ). On the other hand, dental caries and oral health status of adolescents may affect school performance ( 74 ), school absenteeism ( 21 ), and future employment outcome ( 75 ), and consequently health literacy and use of dental care. Finally, other habits, such as smoking ( 35 , 60 , 65 , 66 ) and use of snuff or smokeless tobacco ( 60 ), are also risk factors, as tobacco exposure ( 76 ) is associated with dental caries among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…There is less supervision by parents and more incentive for greater independence in the final years of adolescence. Moreover, there is encouragement to search for one's first job, and adolescents are responsible for making decisions and taking care of their own health [27]. This result is important and suggests the need to strengthen public policies that guide adolescents to seek adequate dental services.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other variables, such as household income, malocclusion, and toothache, had an indirect impact on the labor market entry. 18 Pithon et al 16 developed a study in which participants were shown facial photographs of people with different degrees of malocclusion which were later digitally modified to show ideal smiles. Using a questionnaire, the participant found these corrected images correlated with being more intelligent and having better chances of getting a job.…”
Section: Introductionmentioning
confidence: 99%